Life Cycle and Secondary Production of Four Species from Functional Feeding Groups in a Tropical Stream of South India - Anbalagan, Sankarappan; Dinakaran, Sundaram; Krishnan, Muthukalingan (International Journal of Zoology, 2014)
This study focused on life strategies of species from functional feeding groups (FFGs) found in a tropical stream of the Sirumalai hills, South India. We examined the life cycle and secondary production of species of shredders (Lepidostoma nuburagangai), scrapers (Baetis sp.), collectors (Choroterpes alagarensis), and predators (Neoperla biseriata). In addition, we studied the assemblage structure of functional feeding groups. We found the collectors occupied the highest percentage, followed in turn by scrapers, predators, and shredders. The diversity of FFGs was higher at riffle areas and assemblage with stream substrates differing in each functional group. An asynchronous life cycle was observed for Baetis, C. alagarensis, and N. biseriata, while L. nuburagangai was found in four to five generations per year. We acquired data on secondary production of scraper species of Baetis, which reached the highest values among all investigated species. This observation stresses the importance of scrapers as playing a key role in converting coarse particulate organic matter to fine particulate organic matter with low or high abundances of shredder population and maintaining the food chain in tropical streams.